Hubungan Peer Group Support dengan Perilaku Memilih Jajanan Sehat Pada Anak Sekolah (Kelas VI) di Sdn Jatikramat VI Kota Bekasi - Rana Sandrina; Yulia Agustina (Malahayati Nursing Journal, 2024)
ABSTRACT The behavior of school-age children tends not to be able to sort and choose which snacks are healthy and which are unhealthy. When children are at school, friends play an important role in choosing snacks and parents play an important role in educating children to choose healthy snacks and try to bring provisions. Analyzing and identifying the relationship between peer group support and the behavior of choosing healthy snacks in school-age children (class VI) at SDN Jatikramat VI Bekasi City. Researchers used a cross sectional analytic survey method. The total population of 44 with 40 respondents obtained the results of the Chi Square test showing that there was a relationship between peer group support and the behavior of choosing snacks in grade VI school children at SDN Jatikramat VI Bekasi City in 2023 with a P value of 0.06 (p 0.05).There is a significant relationship between peer group support and the behavior of choosing snacks in class VI students at SDN Jatikramat VI, Bekasi City. Keywords: School Children, Peer Group Support, Behavior of Choosing Snacks  ABSTRAK Perilaku anak usia sekolah cenderung belum bisa memilah dan memilih mana jajanan sehat dan tidak sehat.  Saat anak disekolah, teman berperan penting dalam pemilihan jajanan dan orang tua berperan penting dalam mendidik anak untuk memilih jajanan sehat serta mengupayakan untuk membawa bekal. Menganalisis dan mengidentifikasi hubungan peer group support dengan perilaku memilih jajanan sehat pada anak usia sekolah (kelas VI) di SDN Jatikramat VI Kota Bekasi. Peneliti menggunakan metode survei analitik cross sectional Jumlah populasi keseluruhan 44 dengan 40 responden mendapatkan hasil uji Chi Square menunjukan adanya hubungan peer group support dengan perilaku memilih jajanan pada anak sekolah kelas VI di SDN Jatikramat VI Kota Bekasi pada tahun 2023 dengan P value 0.06 (p0.05). Ada hubungan yang signifikan antara peer group support dengan perilaku memilih jajanan pada siswa-siswi kelas VI di SDN Jatikramat VI Kota Bekasi. Kata Kunci: Anak Sekolah, Peer Group Support, Perilaku Memilih Jajanan